Contrasting sirtuin and poly(ADP‐ribose)polymerase activities of selected 2, 4, 6‐trisubstituted benzimidazoles. (9th August 2017) - Yeong, Keng Yoon; Tan, Soo Choon; Mai, Chun‐Wai; Leong, Chee‐Onn; Chung, Felicia Fei‐Lei; Lee, Yean Kee; Chee, Chin Fei; Abdul Rahman, Noorsaadah
Abstract : Both sirtuin and poly(ADP‐ribose)polymerase (PARP) family of enzymes utilize NAD + as co‐substrate. Inhibitors of sirtuins and PARPs are important tools in drug discovery as they are reported to be linked to multiple diseases such as cancer. New potent sirtuin inhibitors (2, 4, 6‐trisubstituted benzimidazole) were discovered from reported PARP inhibitor scaffold. Interestingly, the synthesized compounds have contrasting sirtuin and PARP‐1 inhibitory activities. We showed that modification on benzimidazoles may alter their selectivity toward sirtuin or PARP‐1 enzymes. This offers an opportunity for further discovery and development of new promising sirtuin inhibitors. Molecular docking studies were carried out to aid the rationalization of these observations. Preliminary antiproliferative studies of selected compounds against nasopharyngeal cancer cells also showed relatively promising results. Abstract : From PARP to Sirtuin inhibitor: Sirtuin and PARP both use NAD + as co‐substrate. PARP‐1 inhibitor can be carefully modified to become potent sirtuin inhibitor.